Ineffectiveness Implementation of Indonesia-Japan Economic Partnership Agreement for Indonesia - Anindya, Vania; Kamsari, Claresta Amantha; Jonathan M. D., Kenneth; Farisqi, M Reval Alfiadi (Research Horizon, 2025)
Indonesia-Japan Economic Partnership Agreement (IJEPA) is a bilateral economic cooperation between Indonesia and Japan that aims to create fair, balanced, and measurable benefits for both countries. This study aims to identify factors that hinder the sustainability and effectiveness of IJEPA implementation. The method used is a qualitative approach with data search via the internet and literature study as the main method of information collection. The results of the study indicate that the implementation of IJEPA has not fully provided optimal benefits for Indonesia. One of the main problems found is that Indonesia has not been able to create a competitive advantage in its industrial sector, which has caused it to lag behind Japan. High dependence on imported raw materials and suboptimal existing production factors are the main obstacles. In addition, the presence of many foreign companies operating in Indonesia also worsens the competitiveness of the domestic industry. Thus, policies and strategic steps are needed that can strengthen Indonesia's competitiveness so that IJEPA can provide greater benefits and support the development of the national industry in a more sustainable manner.